x(x+3x)=8(8+x+2)

Simple and best practice solution for x(x+3x)=8(8+x+2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x(x+3x)=8(8+x+2) equation:


Simplifying
x(x + 3x) = 8(8 + x + 2)

Combine like terms: x + 3x = 4x
x(4x) = 8(8 + x + 2)

Remove parenthesis around (4x)
x * 4x = 8(8 + x + 2)

Reorder the terms for easier multiplication:
4x * x = 8(8 + x + 2)

Multiply x * x
4x2 = 8(8 + x + 2)

Reorder the terms:
4x2 = 8(8 + 2 + x)

Combine like terms: 8 + 2 = 10
4x2 = 8(10 + x)
4x2 = (10 * 8 + x * 8)
4x2 = (80 + 8x)

Solving
4x2 = 80 + 8x

Solving for variable 'x'.

Reorder the terms:
-80 + -8x + 4x2 = 80 + 8x + -80 + -8x

Reorder the terms:
-80 + -8x + 4x2 = 80 + -80 + 8x + -8x

Combine like terms: 80 + -80 = 0
-80 + -8x + 4x2 = 0 + 8x + -8x
-80 + -8x + 4x2 = 8x + -8x

Combine like terms: 8x + -8x = 0
-80 + -8x + 4x2 = 0

Factor out the Greatest Common Factor (GCF), '4'.
4(-20 + -2x + x2) = 0

Ignore the factor 4.

Subproblem 1

Set the factor '(-20 + -2x + x2)' equal to zero and attempt to solve: Simplifying -20 + -2x + x2 = 0 Solving -20 + -2x + x2 = 0 Begin completing the square. Move the constant term to the right: Add '20' to each side of the equation. -20 + -2x + 20 + x2 = 0 + 20 Reorder the terms: -20 + 20 + -2x + x2 = 0 + 20 Combine like terms: -20 + 20 = 0 0 + -2x + x2 = 0 + 20 -2x + x2 = 0 + 20 Combine like terms: 0 + 20 = 20 -2x + x2 = 20 The x term is -2x. Take half its coefficient (-1). Square it (1) and add it to both sides. Add '1' to each side of the equation. -2x + 1 + x2 = 20 + 1 Reorder the terms: 1 + -2x + x2 = 20 + 1 Combine like terms: 20 + 1 = 21 1 + -2x + x2 = 21 Factor a perfect square on the left side: (x + -1)(x + -1) = 21 Calculate the square root of the right side: 4.582575695 Break this problem into two subproblems by setting (x + -1) equal to 4.582575695 and -4.582575695.

Subproblem 1

x + -1 = 4.582575695 Simplifying x + -1 = 4.582575695 Reorder the terms: -1 + x = 4.582575695 Solving -1 + x = 4.582575695 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + x = 4.582575695 + 1 Combine like terms: -1 + 1 = 0 0 + x = 4.582575695 + 1 x = 4.582575695 + 1 Combine like terms: 4.582575695 + 1 = 5.582575695 x = 5.582575695 Simplifying x = 5.582575695

Subproblem 2

x + -1 = -4.582575695 Simplifying x + -1 = -4.582575695 Reorder the terms: -1 + x = -4.582575695 Solving -1 + x = -4.582575695 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + x = -4.582575695 + 1 Combine like terms: -1 + 1 = 0 0 + x = -4.582575695 + 1 x = -4.582575695 + 1 Combine like terms: -4.582575695 + 1 = -3.582575695 x = -3.582575695 Simplifying x = -3.582575695

Solution

The solution to the problem is based on the solutions from the subproblems. x = {5.582575695, -3.582575695}

Solution

x = {5.582575695, -3.582575695}

See similar equations:

| 2x+7x=10x-4 | | Y+2x+10=180 | | 2(n+5)=n+19 | | 5p+2=4-1 | | 7-7q=-15+-9q | | (4y^3-y-1)-(2y^2-3y+7)=0 | | 8y-2=-3(y-3) | | x*x+6x+9=-3x+1 | | 2+12x=123x | | 6-9x=36-13x | | 9st(7s-6t^2)= | | x+6x+9=-3x+1 | | 7(7+6)=x(x+4) | | 180=y+(5x+20) | | -12-15x=33 | | 6(v-9)=-2v-14 | | 9(3n-3)=(4n+8)+2 | | 0.3x+3=-2.3x+0.4 | | 7(x-1)+3(3-x)=5(1-x)-3(2x+1) | | 2(90-x)-6=124 | | 961=400+2x | | 15+5(x-10)=3(x-1) | | 16x+16=16x-16 | | 13t-52+8t=21t+28-10 | | 5(z+1)=z+8 | | 5+-6= | | 180=y+5x+20 | | 12x+4=1(x+12) | | -8x-12=36 | | -11+-9= | | 5x+2(x+7)=6x+14 | | -8z-18=-10 |

Equations solver categories